In vivo Magnetic Resonance Metabolic and Morphofunctional Fingerprints in Experimental Models of Human Ovarian Cancer - Canese, Rossella; Mezzanzanica, Delia; Bagnoli, Marina; Indraccolo, Stefano; Canevari, Silvana; Podo, Franca; Iorio, Egidio (Frontiers in Oncology, 2016)
Epithelial ovarian carcinoma (EOC) is the gynecological malignancy with the highest death rate, characterized by frequent relapse and onset of drug resistance. Disease diagnosis and therapeutic follow-up could benefit from application of molecular imaging approaches such as magnetic resonance imaging (MRI) and spectroscopy (MRS) able to monitor metabolic and functional alterations and investigate the underlying molecular mechanisms. Here we overview the quantitative alterations which occur during either orthotopic or subcutaneous growth of preclinical EOC models. A common feature of 1H MR spectra is the presence of a prominent peak due to total choline-containing metabolites (tCho), together with other metabolic alterations and MRI-detected morphofunctional patterns specific for different phenotypes. The tCho signal, already present at early stages of tumor growth and changes of diffusion-weighted MRI parameters could serve as markers of malignancy and/or tumor response to therapy. The identification by MRS and MRI of biochemical and physiopathological fingerprints of EOC disease in preclinical models can represent a basis for further developments of non-invasive MR approaches in the clinical setting.